PENGARUH STANDAR OPERASIONAL PROSEDUR (SOP) KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN PT. INDOMOBIL FINANCE LAMPUNG TIMUR - Buchori Buchori (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to find out and analyze whether there is an influence of the Standard Operating Procedures (SOPs) on improving the performance of the employees of PT. Indomobil Finance Branch of Way Jepara, East Lampung. Data collection techniques used in this study were observation, questionnaires and documentation. As in this study the population is all employees of PT. Indomobil Finance Branch of Way Jepara, East Lampung, with 15 employees. This study discusses two research variables namely the Standard Operating Procedure (SOP) work and employee performance improvement. The analysis technique in this research is a simple linear regression formula. From the analysis results obtained an R2 value of 0.186, meaning that there is a workmanship Standard Operating Procedure (SOP) Work to increase employee performance by 18.6% and t count 4,410 values when compared with t table where dk = n-1 is 15- 1 = 14 with an error level of 5% the value of t table is 2.145 (Appendix 4) with a sig value 0.05. This means that the Standard Operating Procedure (SOP) work has an influence on improving the performance of employees of PT. Indomobil Finance Branch of Way Jepara, East Lampung.